Massive Orbital Myiasis Caused by Sarcophaga argyrostoma Complicating Eyelid Malignancy. (30th April 2020) - Ayalon, Anfisa; Yehezkeli, Veronika; Paitan, Yossi; Szpila, Krzysztof; Mumcuoglu, Kosta Y.; Moisseiev, Elad
Abstract : Purpose . To report a case of massive orbital myiasis caused by the larvae of Sarcophaga argyrostoma, complicating eyelid malignancy. Observations . A 98-year-old man first presented to our clinic noted to have a fast-growing lesion on his right upper and lower eyelids. Squamous cell carcinoma of the eyelids was highly suspected, and surgical excision was advised, but the patient refused any surgical or nonsurgical intervention. For the next eight months, the patient's family members continued to observe a high rate of tumor growth accompanied by deterioration of the general condition. During this whole period, the patient rejected admission to the hospital and was observed by nursing home staff. He was admitted to the emergency room in cachexic, unresponsive condition with fetid discharge and multiple live maggots crawling out from a large necrotic mass over the right orbit. On examination, no eyelids, eyeball, or other ocular tissue could be seen, while an extension of necrotic mass to forehead and midcheek was noted. Manual removal of larvae was performed. The patient passed away eight hours after his admission and larval removal. The maggots were identified as the third-instar larvae of Sarcophaga argyrostoma . Conclusions and Importance . This is the first reported case of home-acquired, massive orbital myiasis by S . argyrostoma . This case illustrates the crucial role of fly control as part of medical and home care in immobile patients. Moreover, it shows the importance of awareness by nursing home staff, paramedical, and medical personnel of possible myiasis, especially in bed-bound patients with skin malignancies and open wounds.